Evaluation of tax audit strategies - Giriūnienė, Gintarė; Benetytė, Raminta (Buhalterinės apskaitos teorija ir praktika, 2013)
It should be noted that the tax audit topic is relevant – during the last years quantity of tax audits accomplished by state authorities is still growing. Especially in this way is attempted to combat against tax avoidance and evasion, informal economy prevailed in the country. For committing it only helps to have regular inspections of taxpayers i.e. tax audits. Tax audits are divided under the verification time, as it is classified into a complex, a thematic inspection and an operational check. However, despite the existing differences between the various types of tax audit, a key moment of choosing strategy is a tax audit organization. In practice there are distinguished two tax audit strategies – “line-plane-point“ and “point-line-plane“. The first one indicates that before the initial analysis of data examination, it is necessary to investigate whether the company's tax accounting does not have indications for increased risk of error existence. For its practical application is necessary to execute a thorough collection and analysis of the evidence, and the most important is objective and correct assessment of indicators for an increased risk of errors. For this purpose suspicious taxpayers usually are selected and under the tax audit all of the data that can distort selected dubious indicators are checked. In application of the second strategy, if the execution of a company is suspected of tax evasion, it will be forwarded to the additional tax audit services, which will continue the investigation and will explore the additional information. Accomplished practical research have shown that the more of these indicators are observed during initial tax audit stage, the “point-line-plane“ method is more likely to be chosen. Accordingly, to choose one or another tax strategy correctly and adapt it properly it is necessary to take into account the indicators linked to the need for a tax audit.
Keywords: tax audit; tax audit strategies; organization of tax audits; taxpayer classification